Revitalizing Havighurst's social role research - Waynne B. James; Howard M. Abney Jr. (Adult Education Research Conference, 1994)
The purpose of this exploratory research was to update, revise, and content validate Havighurst's classic social role studies for use by educators and education program planners in the 1990s. One major intent of this initial study was to generate hypotheses for further research into adult development and social role performance.